Pengaruh Pemberian Ekstrak Nannochloropsis oculata Terhadap Penurunan Kadar TNF-α pada Tikus yang Diinduksi Bakteri Actinobacillus actinomycetemcomitans - Peggie Octavia Halim; Syamsulina Revianti; Yoifah Rizka Wedarti (Denta Journal Kedokteran Gigi, 2015)
Background: Actinobacillus actinomycetemcomitans is a major periodontopathic bacterium with multiple virulence factors, including LPS. LPS is a potent stimulator cytokines proinflammatory such as TNF-α. Nannochloropsis oculata is a green micro algae that hasanti-inflammatory effects. Purpose: The aim of this study was to prove the effect of Nannochloropsis oculata extracts to decreased levels of TNF-α which induced by Actinobacillus actinomycetemcomitans bacteria. Materials and Methods: The experiment was held post test only control group design. 48 male wistar rats divided into 6 groups. K1 group was negative control group without any treatment, K2 group induced by Actinobacillus actinomycetemcomitans bacteria, K3 group treated with minocycline antibiotics 0.1%, and the other groups K4, K5, K6 were treated with Nannochloropsis oculata extract on various concentration that is 2.375%, 2.5%, 2.625%. After treatments on the 37th day, all groups of rats were euthanized and measured the levels of TNF-α in gingival tissue by ELISA. All of thedatas were analyzed by Kruskal Wallis dan Mann-Whitney U test. Result: This study showed the levels of TNF-α K2 group (36.9444) was significantly higher than K1 group(27.8889). K3 group (29.2778) showed no significant decreased compared to K2 group (36.9444). K4 (35.2778), K5 (33.1111) and K6 (29.2778)groups showed no significant decreased levels of TNF-α compared to K2 group (36.9444). Conclusion: Nannochloropsis oculata extracts can not reduce the levels of TNF-α in rats which induced by Actinobacillus actinomycetemcomitans bacteria.